Нові результати про інклюзивне народження пар кварконіуму в протон-протонних зіткненнях - Schäfer, W.; Babiarz, I.; Cisek, A.; Szczurek, A. (Publishing house "Academperiodika", 2019)
Recently, there has been much interest in the pair production of charmonia. One of the main motivations behind these studies is that the production of quarkonium pairs is expected to receive an important contribution from the double parton scattering (DPS) production mode. A large effective cross-section qeff is found from the empirical analysis of the J/ф-pair production – about a factor 2.5 smaller than the usually accepted qeff = 15 mb. Here, we present the recent results of our calculations of the xc pair production, mainly in the single parton scattering (SPS) mode. An important feature is that the single-gluon exchange mechanism can to some extent mimic the behavior of the DPS production.